The Correlation Between Coping Mechanism And Anxiety Levels On Parents Having Mental Retardation Children In SLB BC PGRI Sumber Pucung - Ardani, Windia Ari; Sasono, Tri Nurhudi; Rohmi, Faizatur (Universitas Islam Lamongan, 2020)
Parents who have mentally retarded children may occur at home and in the community. When this happens the parents become anxious, lose self-esteem, and experience high stress. The psychological adaptive response of the stressor is called coping eating. This study aims to determine the relationship of coping mechanisms with the level of anxiety of parents who have mentally retarded children. The research design uses non-correlational experiments with cross sectional approach. The population is all parents who have mentally retarded children as many as 50 respondents. Sampling of 50 respondents using the Total Sampling technique. The instrument uses the COPE Inventory and DASS questionnaire. Data analysis techniques using the Spearman Rank. Most parents have adaptive coping mechanisms as many as 26 respondents (52%) and experience moderate anxiety as many as 22 respondents (44%). Statistical tests indicate the magnitude of the correlation coefficient between the two variables is 0.443 with a significant value of 0.001 <0.05. These results indicate that there is a correlation between coping mechanisms with anxiety of parents who have mental retardation children in SLB BC PGRI Sumber Pucung.The existence of the results of this study, it is expected that parents always use adaptive coping mechanisms to overcome their anxiety.